2022
DOI: 10.3389/fcvm.2022.754909
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiogram-Based Heart Age Estimation by a Deep Learning Model Provides More Information on the Incidence of Cardiovascular Disorders

Abstract: ObjectiveThe biological age progression of the heart varies from person to person. We developed a deep learning model (DLM) to predict the biological age via ECG to explore its contribution to future cardiovascular diseases (CVDs).MethodsThere were 71,741 cases ranging from 20 to 80 years old recruited from the health examination center. The development set used 32,707 cases to train the DLM for estimating the ECG-age, and 8,295 cases were used as the tuning set. The validation set included 30,469 ECGs to foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 44 publications
2
42
0
Order By: Relevance
“…The first strategy was the standard oversampling process without any revision in each batch (no-match), and the initial parameters were generated at random. The second strategy was to use the first strategy with transfer learning via age estimation DLM (no match with transfer), which was based on a previous study [ 46 ]. The third strategy was to additionally match both sex and age (sex-/age-matched).…”
Section: Methodsmentioning
confidence: 99%
“…The first strategy was the standard oversampling process without any revision in each batch (no-match), and the initial parameters were generated at random. The second strategy was to use the first strategy with transfer learning via age estimation DLM (no match with transfer), which was based on a previous study [ 46 ]. The third strategy was to additionally match both sex and age (sex-/age-matched).…”
Section: Methodsmentioning
confidence: 99%
“…Such results at least superficially correspond to the findings in our study that the Heart Age Gap increased with increasing burden of cardiovascular risk. Other DNN-based AI methods, similar to that of Attia et al also more recently reported similarly encouraging results 10 , 13 , 14 .…”
Section: Discussionmentioning
confidence: 54%
“…Or the extent to which unanticipated results might merely relate to excess dependency on the particular characteristics of a given DNN AI model’s training set 50 . In addition, a major flaw in all DNN-based AI ECG age models that we are aware of is that their age predictions were made using training datasets that also included individuals with both cardiovascular risk factors and established disease 8 , 10 , 13 , 14 . For ECG Heart Age to be used as a marker of potentially reversible cardiovascular disease and risk, it is imperative that ECG Heart Age agrees with chronological age in healthy populations, since it is the deviation from the line of identity in this relationship that forms the basis for measurement-related accuracy and precision, and subsequent disease-related assessment and risk.…”
Section: Discussionmentioning
confidence: 99%
“…As the AI-ECG could predict the disease development in healthy individuals without abnormal imaging findings or symptoms, the concept of previvors was proposed recently. With apparent false positive AI-ECG findings, patients with a higher risk of many diseases, such as LV dysfunction ( 20 ), future atrial fibrillation ( 63 ), hyperkalemia ( 64 ), and elder heart age ( 44 ), could receive preventive interventions or medical surveillance early.…”
Section: Discussionmentioning
confidence: 99%
“…The demographic characteristics were obtained in our EMRs and disease history before the index date of ECG was collected using the corresponding code of International Classification of Disease, Ninth Revision and Tenth Revision (ICD-9 and ICD-10, respectively), as described previously ( 24 , 26 , 32 , 44 ). The remaining echocardiographic parameters, such as interventricular septum (IVS) diameter, left ventricular posterior wall (LVPW) diameter, left atrium (LA) size, aortic root (AO) diameter, right ventricular (RV) diameter, pulmonary artery systolic pressure (PASP), and pericardial effusion (PE), were also collected in this study.…”
Section: Methodsmentioning
confidence: 99%